HUBUNGAN LABA BERSIH, ARUS KAS OPERASI, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI PERIODE 2021 - 2023 - Munika, Rani; Kasmadi, Kasmadi; Pirmansyah, Pirmansyah; Helmiati, Helmiati; Wahyu, Wadri (Komunitas Manajemen Kompetitif, 2025)
This study aims to examine the effect of net income, operating cash flow, and company size on dividend policy in LQ45 companies during the period 2021 - 2023. This research uses quantitative methods with secondary data as the source. The sample in this study was 22 using the puosive sampling method. The data analysis technique used is multiple linear analysis. The results showed that simultaneously, independent variables such as net income, operating cash flow, and company size have an influence on the dependent variable, namely Dividend Policy. Partially, net income and company size have a significant effect on dividend policy, while operating cash flow has no significant effect on dividend policy